9y-14=6y-2

Simple and best practice solution for 9y-14=6y-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9y-14=6y-2 equation:


Simplifying
9y + -14 = 6y + -2

Reorder the terms:
-14 + 9y = 6y + -2

Reorder the terms:
-14 + 9y = -2 + 6y

Solving
-14 + 9y = -2 + 6y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6y' to each side of the equation.
-14 + 9y + -6y = -2 + 6y + -6y

Combine like terms: 9y + -6y = 3y
-14 + 3y = -2 + 6y + -6y

Combine like terms: 6y + -6y = 0
-14 + 3y = -2 + 0
-14 + 3y = -2

Add '14' to each side of the equation.
-14 + 14 + 3y = -2 + 14

Combine like terms: -14 + 14 = 0
0 + 3y = -2 + 14
3y = -2 + 14

Combine like terms: -2 + 14 = 12
3y = 12

Divide each side by '3'.
y = 4

Simplifying
y = 4

See similar equations:

| -3w+11=-8w+51 | | y=7x^2-4x | | 7x-5y-10=0 | | 24=-11y-8+3y | | 60*0.2= | | 3w-4=-16 | | -32=w/5-7 | | -v+131=180 | | 31=-u+184 | | 205=96-y | | -25=4u+3 | | 82-(4-6)2= | | 25n^8-49n^7-2n^6=0 | | -3+w=-4 | | -6=u-4 | | 5(2x-9)+3x=4x-18 | | 13=0.5((4x-10)+(3x+8)) | | 9x-(x+4)=2x+32 | | (1/7(x))+((1/7)x+1)+29=x | | 2x^1/2-7x^1/4+3=0 | | 63=.5h*9 | | 4x+7=54 | | 1/2*(3/5((2^3)-6))+1/5 | | 7/5x^2-7/9x-4/3x | | 1/2*3/5((2^3)-6)+1/5 | | 82x+4x=68.5 | | 5y+1/9=6y+5/9 | | 0.50x+0.05(80)=0.25(64) | | -8(x+5)+3=-37 | | 5x/14-3x/14-11x/14= | | -3x+2y+z=4 | | (3x+2)(5x-1)= |

Equations solver categories